Grammar of Valences and Dialect Syntax in the Galician-Portuguese Realm: some Practical Examples - Sánchez Rei, Xosé Manuel (Madrygal. Revista de Estudios Gallegos, 2020)
Since its emergence as a linguistic discipline in the 19th century, Dialectology focused especially on phonetic, morphological and lexical phenomena. Syntax, despite its importance as one of the central components of the grammar, was practically forgotten in the classic works of Dialectology, and not only in the Galician-Portuguese space, but also in other languages. The Grammar of Valences, one of the most relevant language schools of the 20th century, can favor the investigation of dialectal syntactic phenomena. To do this, we must start from the syntactic importance and semantic characteristics of the verbs and see how the dialectal variations are manifested in their predicative frames.
Keywords: Dialectology; Galician-Portuguese Linguistic Space; Grammar of Valences; Syntax